How do people experience innocent suffering? - Smirnov, Evgeny (Frontiers in Psychology, 2023)
The paper examines the psychological facet of innocent suffering. One can find a description of this phenomenon in social psychology as a factor that affects the belief in a just world, but there is a lack of qualitative scientific data about related psychological features, processes, copings, and consequences on the personality level. To study innocent suffering, a semi-structured in-depth interview was conducted (31 respondents, 223 minutes per respondent, 6924 minutes in total) aimed to gather data about the experiences of innocent sufferings happened to participants. For the analysis of texts, a narrative and content analysis are used within the framework of grounded theory. The reliability of the results is based on expert assessment. As a result, six essential properties of innocent sufferings were identified: complexity, stability, distress, injustice, casual incoherence, and breaks of integrity of a life story. The most 'popular' life domains, in which participants reported about innocent sufferings, are violence, abuse (physical and psychological), and quitting romantic relationships. It is proposed a scientific definition of innocent suffering and the prototype of the phenomenon.